Analisis Dampak Pembelajaran Daring Terhadap Hasil Belajar Geografi Siswa SMAN 2 Labuapi pada Masa Pandemi Covid-19 - Zaedun Zaedun (Universitas Pendidikan Mandalika, 2022)
This study aims to analyze the impact of online learning on student learning outcomes in the Geography subject, the subject matter of Population Data Processing and Analysis in class XI IPS SMAN 2 Labuapi during the Covid-19 pandemic. This research method uses a descriptive method with a qualitative approach. The subjects of this study were students of class XI IPS 1, totaling 30 people. Data collection techniques using observation, documentation, and interviews. While the data analysis technique using interactive analysis includes data reduction, data presentation, and drawing conclusions. The results showed that online learning had an impact on student learning outcomes on the subject matter. Population Data Sources learning outcomes of 30 students showed 93% of students achieved completeness and only 7% had not. The average value of student learning achievement in this subject matter reached 81.83.